PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI (STUDI PADA NASABAH KUR MIKRO BRI UNIT KEC. RUNGKUT, SURABAYA TIMUR) - REZKI ANANDA PETRO, ANDI (Jurnal Ilmu Manajemen (JIM), 2018)
Various banking services are emerging with a variety of services quality offered, which causes competition in the banking services world to be increasingly stringent. Bank Rakyat Indonesia (Persero) is one of the most trusted banks and has the widest network, so consumers will be easier to make transactions compared to their competitors. Although the products offered are in accordance with the expectations of the community, poor service can affect customer confidence in the product which affects the loss of customer satisfaction. This study aims to analyze and discuss the effect of service quality on satisfaction with trust as a mediating variable. This study aims to analyze and discuss the effect of service quality on satisfaction with trust as a mediating variable. This study uses conclusive research with a number of respondents 105, then analyzed qualitatively and sampling with non-probability sampling techniques. The measurement scale used in this study is the Likert scale. Statistical analysis in this study uses path analysis (Path Analysis) using software AMOS 20. The results of this study indicate that there is a significant effect on service quality variables on the trust variable, there is a significant effect of the trust variable on the satisfaction variable and there is a significant influence between the service quality variable on the satisfaction variable. Keywords: customer satisfaction; service quality; trust